A STUDY OF RECOVERY FACTOR CALCULATION FOR PARTIALLY-DEPLETED RESERVOIR WITH A CASE STUDY FROM THREE WELLS IN FIELD Y. - PRASETYO WIJAYANTO (NIM : 12299007), DODHY
Determination of recovery factor at certain reservoir pressure is highly necessary for companyÃ‚Â’s economic analysis, because the amount of oil or gas volume that could be recovered to the surface (remaining reserve) until a reservoir has reached its abandonment pressure from its pressure could be seen from the recovery factor by multiplying recovery factor with the remaining oil or gas volume at that certain pressure. API equation that was issued in 1967 by American Petroleum Institute and analytical equation are going to be applied in order to calculate recovery factor. To calculate recovery factor for partially-depleted reservoir, the result from API equation should be corrected by having a correction factor from Reservoir Simulation Correction Method or from Pressure Correction Method. There is a different between the final result using analytical equation and using corrected API equation. The different could be used as a comparison and a reference in determining the range of recovery factor. Eventually remaining reserve of a reservoir at a certain pressure could be determined.